Effect and mechanism of cyclodextrins on nitrate reduction and bio-activity by S.oneidensis.MR-1. (December 2020) - Tu, Jun; Guo, Jianbo; Lu, Caicai; Li, Haibo; Song, Yuanyuan; Han, Yi; Hou, Yanan
Graphical abstract: Highlights: Nitrate reduction of S.oneidensis.MR-1 was enhanced by CDs. The mechanism of β-CD on nitrate reduction was studied. More EPS of S.oneidensis.MR-1 was stimulated by β-CD. The cell membrane permeability of S.oneidensis.MR-1 was increased by β-CD. The β-CD enhanced ETSA and NAR activity. Abstract: Cyclodextrins (CDs) have been widely used due to the excellent solubilization of hydrophobic organics. However, their effect on the biotransformation process of hydrophilic pollutants is unclear. This study first evaluated the effect and mechanism of CDs on nitrate reduction by S.oneidensis.MR-1 . The three CDs (α-CD, β-CD and γ-CD) all accelerated nitrate reduction, among which β-CD had the best effect. The nitrate reduction rate was increased by 21.8% with 0.5 mM β-CD. As for the mechanism, β-CD increased the biomass, membrane permeability and EPS of S.oneidensis.MR-1 . The nitrate reductase activity was also increased by 1.34-fold with 0.5 mM β-CD. The current exchange density and the electron transfer system activity were increased by 11.4% and 99.5% in the β-CD-supply system, respectively. It confirmed that β-CD enhanced the biological and electrochemical characteristics and then enhanced bio-activity. This study provides a new understanding of CDs in microbial remediation and broadens the practical application.